2018
DOI: 10.1007/s12192-018-0917-y
|View full text |Cite
|
Sign up to set email alerts
|

Sirt3 inhibits cerebral ischemia-reperfusion injury through normalizing Wnt/β-catenin pathway and blocking mitochondrial fission

Abstract: Cerebral ischemia-reperfusion injury (IRI) potentiates existing brain damage and increases mortality and morbidity via poorly understood mechanisms. The aim of our study is to investigate the role of Sirtuin 3 (Sirt3) in the development and progression of cerebral ischemia-reperfusion injury with a focus on mitochondrial fission and the Wnt/β-catenin pathway. Our data indicated that Sirt3 was downregulated in response to cerebral IRI. However, the overexpression of Sirt3 reduced the brain infarction area and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 67 publications
3
35
0
Order By: Relevance
“…However, excessive mitochondrial fission produces a large amount of mitochondrial fragments, which are harmful to the homeostasis and functions of cells. Excessive mitochondrial fission has been reported to be involved in brain IRI, serving as a primary contributor to cerebral IRI-induced neuronal death 28 . In this study, by observing mitochondrial length and measuring the expression of mitochondrial fission-associated proteins 29 , we found that activation of the cannabinoid CB1 receptor using ACEA reduced OGD/R-or brain ischemia-induced mitochondrial fission and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, excessive mitochondrial fission produces a large amount of mitochondrial fragments, which are harmful to the homeostasis and functions of cells. Excessive mitochondrial fission has been reported to be involved in brain IRI, serving as a primary contributor to cerebral IRI-induced neuronal death 28 . In this study, by observing mitochondrial length and measuring the expression of mitochondrial fission-associated proteins 29 , we found that activation of the cannabinoid CB1 receptor using ACEA reduced OGD/R-or brain ischemia-induced mitochondrial fission and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Focal cerebral ischemia/reperfusion injury was performed as described previously 28 . The treatment of the animals conformed to the Committee on Publication Ethics guidelines.…”
Section: Ischemic Brain Injury Modelmentioning
confidence: 99%
“…Findings from rat models of TBI have revealed that ceramide is the first lipid to accumulate in the mitochondria after TBI (Roux et al, 2016), suggesting it may serve as a therapeutic indicator (Barbacci et al, 2017). Ceramide accumulation causes mitochondrial dysfunction (Novgorodov et al, 2016), which is associated with increased mitochondrial fission and excessive ROS production (Zhao et al, 2018). According to existing research, SIRT1 and SIRT3 have been detected to alleviate oxidative stress in TBI models (Rangarajan et al, 2015;Zou et al, 2018).…”
Section: Sirtuins Improve Mitochondrial Function and Reduce Oxidativementioning
confidence: 99%
“… 22 Elevated Sirt3 blocks mitochondrial fission in cerebral ischemia–reperfusion via suppressing the Wnt/β-catenin pathway. 23 In contrast, Sirt3 deficiency exacerbates p53-related mitochondrial dysfunction in aged hearts. 24 However, whether Mst1 has a role in regulating mitochondrial fission via the AMPK-Sirt3 pathway is not clear.…”
Section: Introductionmentioning
confidence: 99%